Protective effect of Glycyrrhiza glabra L. root (licorice) extract against severe acute pancreatitis-induced acute lung injury via suppressing autophagy and inflammation - Nourhan Gamal EL-Rahmany; Eman Hassan Abdel Aziz Sharaf (Shahrekord University of Medical Sciences, 2023)
Introduction: Acute pancreatitis (AP) is an inflammatory disease with a high incidence of morbidity and mortality rate. The present study aimed to evaluate the protective effect of licorice extract administration on L-arginine-induced AP and associated lung tissue damage in rats. Methods: The experimental groups were the healthy control group (G1), L-arginine group (G2), licorice extract group (G3), and licorice extract +L-arginine; (protection group; G4). The protective effect of licorice extract was evaluated by measuring serum amylase and lipase, oxidative stress markers (malondialdehyde, nitric oxide, and myeloperoxidase), and inflammatory biomarkers levels (interleukin-6, tumor necrosis factor-alpha, toll-like receptor 4, and vascular cell adhesion molecule 1), as well as apoptosis assessment via caspase-3 activity and beclin-1 expression. Furthermore, an immunohistochemical assessment of heme oxygenase-1 (HO-1) and a histopathological examination of lung and pancreatic tissues were performed. Results: Licorice extract administration significantly reduced serum amylase, lipase, and inflammatory markers levels that pointed to the local and systemic inflammatory condition of AP induced by L-arginine. Moreover, the administration of licorice extract reversed the significant elevation in oxidative stress markers levels in the pancreas and lung tissues. Furthermore, licorice extract downregulated pancreatic gene expression of beclin-1 and caspase-3 which reversed dysregulated pancreatic autophagy. Conclusion: Licorice extract administration causes modulation of oxidative damage and systemic inflammation associated with acute pancreatic damage. Moreover, licorice extract markedly decreases the biochemical and histopathologic changes in AP, preserving the pancreatic and lung tissues through its antioxidant, anti-inflammatory, and antiapoptotic effects.